Composition and mutagenicity of PAHs associated with urban airborne particles in Córdoba, Argentina - Carreras, Hebe Alejandra (2013)
The comet assay and micronucleous test were used to assess the genotoxicity of organic compounds associated with particulate material collected in the city of Córdoba, Argentina. Samples were collected on fiber glass filters and their organic extracts were analyzed by GC-MS. These extracts were used for the comet assay on human lymphocytes and for the MCN test with Tradescantia pallida. The concentrations of polycyclic aromatic hydrocarbons as well as some of their nitro derivates were higher during winter. Their composition suggested that their main emission sources were gasoline and diesel vehicles. We observed genotoxic effects of these organic extracts due to the presence of both direct and indirect acting mutagens. We found a good agreement between the two test systems employed, which encourages the further use of plant bioassays for air pollution monitoring, especially in developing countries, due to their flexibility, low cost and efficiency.